The identity of Kalanchoe crenata that has the name Vereia crenata as its basionym (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae), with analyses of aspects of its taxonomy, and the homotypic synonyms of, and designations associated with, K. crenata - Smith, Gideon F. (Phytotaxa, 2026)
In 1907 / 1908, in the first modern monograph published on the genus Kalanchoe (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae]), Raymond-Hamet succeeded in bringing together virtually all the names—both pre- and post-Linnaean—that had been published for representatives of the genus. Of the former there were very few, and of the latter there were 141, some of which at first had been published in other genera that are at present included in the synonymy of Kalanchoe. While Raymond-Hamet’s work was a significant milestone in the taxonomy of Kalanchoe, in a few instances his very broad concepts of some taxa eventually caused headaches down the line—he recognised only 52 species and one nothospecies (for which the 141 names were available), with a further 10 species treated as “Species non satis notæ”. For example, Raymond-Hamet treated K. laciniata, the type of which is the type of the genus name Kalanchoe, as including a vast range of taxa, several of which, with the knowledge of hindsight, do not belong in the synonymy of K. laciniata. The name K. crenata, which was based on Vereia crenata, was one of the names that Raymond-Hamet included in the synonymy of K. laciniata. Kalanchoe crenata was one of the earliest known (if not one of the earliest described) species of Kalanchoe and holds a central position in the taxonomy of the genus. In addition, the type of the name K. crenata is the type of the genus name Vereia, a heterotypic synonym of Kalanchoe. The nomenclature and aspects of the taxonomy of K. crenata are dealt with in this paper, inter alia through a correction to the sort of type of its basionym, i.e., V. crenata, and a discussion of its homotypic synonyms and the designations associated with the name. This paper paves the way to publish a name for South African material to date treated as K. crenata, and is part of further work to stabilise the nomenclature and taxonomy of Kalanchoe, a genus of considerable global economic importance in the horticultural trade and in invasions biology.